Penerapan Konseling Islam Dengan Teknik Modelling Dalam Mengatasi Al-annanah Pada Penerima Manfaat Penyandang Disabilitas - Dila Julianti; Abdur Razzaq; Lena Marianti (Journal of Society Counseling, 2023)
Al-annanah is often faced by individuals with disabilities, which can affect their psychological well-being and quality of life. The application of Islamic counseling will provide a strong framework of values ​​and principles in guiding participants in understanding and overcoming their al-annanah with a view that is in accordance with Islamic teachings. This research is entitled "Implementation of Islamic Counseling with Modeling Techniques in Overcoming Al-annanah in Persons with Disabilities at the Budi Perkasa Center Palembang". The purpose of this research is to find out how the description of the condition of Al-annanah in persons with disabilities and to find out how the application of Islamic counseling with Modeling Techniques in dealing with Al-annanah in persons with disabilities. The method in this study uses a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews and documentation. The data analysis technique in this study uses the theory of Miles and Huberman. This data analysis technique consists of data reduction, data presentation, and drawing conclusions. The results of this study are expected to provide a better understanding of the effectiveness of applying Islamic counseling with modeling techniques in overcoming al-annanah in persons with disabilities. These findings can make important contributions to counseling practitioners, especially in expanding existing counseling approaches and improving services aimed at this population.